What are the sources of stress and distress for general practitioners working in England? A qualitative study. Issue 1 (5th December 2017) - Riley, Ruth; Spiers, Johanna; Buszewicz, Marta; Taylor, Anna Kathryn; Thornton, Gail; Chew-Graham, Carolyn Anne
Abstract : Objectives: This paper reports the sources of stress and distress experienced by general practitioners (GP) as part of a wider study exploring the barriers and facilitators to help-seeking for mental illness and burnout among this medical population. Design: Qualitative study using in-depth interviews with 47 GP participants. The interviews were audio-recorded, transcribed, anonymised and imported into NVivo V.11 to facilitate data management. Data were analysed using a thematic analysis employing the constant comparative method. Setting: England. Participants: A purposive sample of GP participants who self-identified as: (1) currently living with mental distress, (2) returning to work following treatment, (3) off sick or retired early as a result of mental distress or (4) without experience of mental distress. Interviews were conducted face-to-face or over the telephone. Results: The key sources of stress/distress related to: (1) emotion work—the work invested and required in managing and responding to the psychosocial component of GPs' work, and dealing with abusive or confrontational patients; (2) practice culture—practice dynamics and collegial conflict, bullying, isolation and lack of support; (3) work role and demands—fear of making mistakes, complaints and inquests, revalidation, appraisal, inspections and financial worries. Conclusion: In addition to addressing escalating workloads through the provision of increased resources, addressing unhealthy practice cultures is paramount. Collegial support, a willingness to talk about vulnerability and illness, and having open channels of communication enable GPs to feel less isolated and better able to cope with the emotional and clinical demands of their work. Doctors, including GPs, are not invulnerable to the clinical and emotional demands of their work nor the effects of divisive work cultures—culture change and access to informal and formal support is therefore crucial in enabling GPs to do their job effectively and to stay well.